Similar Construction Method of Solution for Solving the Mathematical Model of Fractal Reservoir with Spherical Flow - Cui-Cui Sheng; Jin-Zhou Zhao; Yong-Ming Li; Shun-Chu Li; Hu Jia (Journal of Applied Mathematics)
On the basis of similar structure of solution for a second-order linear differential equation's boundary value problem, and our analysis of the relationship between this similar structure and its kernel function, the differential equation, and the boundary conditions, we propose a new simple solution—similar constructive method of solution (SCMS)—and sum up its detailed steps. We set up a porous media model under three kinds of outer boundary conditions (infinite, constant pressure, and closed), in which the influences of fractal dimension, spherical flow, skin effect, and storage are taken into consideration. And then we use SCMS to solve it. The SCMS is a straightforward method for differential equation's boundary value problems with complex boundary conditions, especially for solving the reservoir models in petroleum engineering.